The effectiveness of an online e-health application compared to attention placebo or Sertraline in the treatment of Generalised Anxiety Disorder - Helen Christensen; Andrew J. Mackinnon; Philip J. Batterham; Bridianne O'Dea; Adam J. Guastella; Kathleen M. Griffiths; Claire Eagleson; Kanupriya Kalia Hehir; Justin Kenardy; Kylie Bennett; Ian Hickie (Internet Interventions, 2014)
Background: Generalised Anxiety Disorder (GAD) is a high prevalence, chronic disorder that can be treated effectively through a number of web-based programs. However, online web programs for GAD have not been compared to standard pharmacological treatment. The present study compares an Internet Intervention (Active Website) for GAD and a selective serotonin re-uptake inhibitor (SSRI) (Sertraline), with an online attention placebo condition (Control Website). Objective: To evaluate the effectiveness of a web-based intervention for GAD in comparison to standard antidepressant medication and an online attention placebo condition over a 10 week period, and with a follow-up at 6 and at 12 months. Methods: The study was part of a larger scale prevention program. 152 people aged 18–30 years who met the criteria for GAD on the MINI received referrals to the treatment sub-study. The primary outcome was anxiety symptoms measured by the Generalised Anxiety Disorder 7-item Scale (GAD-7), and the secondary outcome was depression measured by the Center for Epidemiologic Studies Depression Scale (CES-D). Results: There was very poor uptake to the trial (around 14% of those referred). However, even in this small sample, Sertraline compared to the Control Website was significant at post-test and 6 months, and the Internet Intervention was significant at post-test. Relative to the Control Website condition at post-test, for the GAD-7 and CES-D respectively, the between group effect sizes were d = 2.43 and d = 0.68 for the Active Website condition, and 3.00 and 0.20 for the Sertraline condition. The within group effect size for the Control Website from baseline to post-test was −0.04 for the GAD-7 and 0.31 for CES-D respectively. Conclusions: The findings will need to be extended and confirmed in a larger trial. However, they do suggest that both standard pharmacological treatment and online interventions for GAD are effective in samples with a diagnosis of GAD recruited via online methods. The low rate of engagement for face-to-face treatment by those who opt first for a web program suggests that treatment preferences are important in help-seeking.